A geography of time: the temporal misadventures of a social psychologist, or how every culture keeps time just a little bit differently - Levine, Robert (England, 2006)
The book intents to seek understanding on the richness and complexity of views about time and the pace of life among culture and cities and people around the world.
Keywords: Culture; Quality Of Life; Quality Of Time